A new role for orthopaedic surgeons: ongoing changes, lessons learned, and perspectives from a level-i trauma center during the COVID-19 pandemic (2020)
The COVID-19 pandemic has redefined global healthcare. With almost 13 million confirmed cases worldwide, medical professionals have been forced to modify their practice to take care of an expanded, critically ill population. Institutions have been challenged to implement innovative ways to maximize the utility and the safety of residents and personnel. Guided by lessons learned from prior mass causalities, war, and previous pandemics, adjustments have been made in order to provide optimal care for all patients while still protecting limited resources and the lives health of workers. Specialists who are trained in the management of lethal aspects of this disease continue to have a high demand and obvious role. Orthopedic surgeons, with ill-defined roles, have been redeployed to manage complex medical problems. Still, the need to manage trauma, fractures, infections, tumors, and dislocations remains a necessity. Various innovative measures to maximize the utility and safety of residents in the inpatient and outpatient setting. Commonalities to most measures and distinct changes in practice philosophy can be identified and applied to both current and future pandemic responses.